2021
DOI: 10.1128/jcm.01564-21
|View full text |Cite
|
Sign up to set email alerts
|

Routine Antigen Testing Is Not a Substitute for Health Care Worker Vaccination against SARS-CoV-2

Abstract: The utility of rapid antigen testing for SARS-CoV-2 is measured within the context for which it is applied; diagnostic accuracy must be considered in determining if rapid antigen testing is appropriate for the clinical situation. In this issue of the Journal of Clinical Microbiology , J.N. Kanji et al (J Clin Microbiol 59:e01411-21, 2021, https://doi.org/10.1128/JCM.01411-21 ) evaluate two rapid antigen tests that demonstrate high false-positive rates in asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Concerns for false positives have also been reported for lateral flow antigen assays. In a screening study with 71,847 tests, the Abbott and BD direct antigen assays showed 30–77% false positive rates in a low prevalence setting (0.05%) [18] . Following these observations, it may be prudent to perform confirmatory RT-PCR tests in a low prevalence setting.…”
Section: Discussionmentioning
confidence: 98%
“…Concerns for false positives have also been reported for lateral flow antigen assays. In a screening study with 71,847 tests, the Abbott and BD direct antigen assays showed 30–77% false positive rates in a low prevalence setting (0.05%) [18] . Following these observations, it may be prudent to perform confirmatory RT-PCR tests in a low prevalence setting.…”
Section: Discussionmentioning
confidence: 98%